Analisis Faktor-Faktor Yang Berhubungan dengan Kekambuhan pada Skizoprenia: Analysis of Factors Associated with Relapse in Schizophrenia - Dewi Eka Putri; Feri Fernandes (Fakultas Keperawatan Universitas Andalas, 2020)
In Indonesia, the incidence of schizophrenia has increased every year. Conditions for an increase in schizophrenia cases also occur in West Sumatra. One problem in treating schizophrenia is recurrence. Many factors cause recurrence in people with schizophrenia (ODS). This study aims to analyze the factors associated with recurrence in schizophrenia patients in West Sumatra. Analytic research design with a cross-sectional study approach. The study sample was 145 patients with schizophrenia and their families who visited the outpatient clinic HB RSJ. Saanin Padang. Data collection using family support questionnaires, Level of Expression Emotion, family attitudes, and medication adherence. The results showed a median recurrence score of 1.00, which meant that the patient had a recurrence, average family support of 74.27, an average family attitude of 33.21, an average medication adherence of 9.92 as well as and an average level of emotional expression was 140. There was an association found meaningful between recurrence with medication adherence and the level of emotional expression of the family. Still, there is no relationship between recurrence with family support and family attitudes. It expected that nurses will help patients improve medication adherence and train families to reduce the level of emotional expression in treating patients with schizophrenia.